Life-saving early diagnosis in the dental chair: Diffuse large B-cell lymphoma in the maxillary sinus - Károly Mensch; Péter Schmidt; Péter Farkas; Katalin Károlyházy (Hungarian Dental Association, 2021)
Non-Hodgkin's lymphomas are rare forms of the head and neck malignancies. It is often accidentally diagnosed or in an advanced phase by the onset of clinical symptoms. It is possible to diagnose it during stomato-oncological screening if it is to spread towards the oral cavity. This paper presents the diagnostic steps, oncological care, and complete dental rehabilitation of a patient, with diffuse large B-cell lymphoma localised in the maxillary sinus. The course of the treatment was mainly determined by the patient's underlying disease. At the end thanks to the early diagnosis and the successful oncological treatment, started on time, the tumour showed complete remission and after eighteen months, no relapse occurred. The patient's general condition is good, he is satisfied with the completed dental restorations and dental works and he is regularly monitored by his doctors.